Traumatismos alveolodentários na dentição decídua : estudo epidemiológico em pré-escolares da rede municipal e privada de ensino de Pelotas-RS - Wendt, Flávia Prietsch (2008)
Epidemiological studies show that dental trauma have become a public health issue. This research aimed to determine the prevalence and distribution of dental injuries in the primary dentition of both male and female children between 12 and 71 months old enrolled in public as well as private pre-schools in Pelotas, RS. Once the Informed Consent Agreement was signed by the children s parents and the research was approved by the Research Ethics Committee, a cross-sectional study was conducted with a 571 children sample, 236 of whom from 8 public schools, and the remaining 335 from 12 previously selected private schools. Data collection was based on a questionnaire directed to the children s parents and on visual examination of the anterior primary teeth. The Andreasen and Andreasen classification of dental trauma (2001) was adopted, and data related to dental discoloration and fistulas were added. A 36,6% prevalence of de dental trauma was found, with no significant male female differences. The private pre-school children presented a higher injury prevalence. The most frequent trauma was enamel fracture and tooth 61 had the greatest incidence. A significant statistical association between trauma and trauma report by private school children parents was found. In the presence of dental trauma, the percentage of parents who sought professional assistance was higher among those whose children studied in private schools rather than those from public ones, which attests to the significant difference between the two pre-school systems in relation to procedure ( p = 0,001). The location and most common etiology mentioned were respectively the children s homes and children s own height falls, both in children from public and private pre-schools. A significant statistical association between trauma and mothers schooling or income was not found. In this prevalence study, dental trauma in primary dentition were characterized by accidents that occur due to the specific development phase children go through, regardless of their mothers schooling or income. But income and schooling wererelevant in the perception of these traumas and in the search for professional assistance